(untitled) (Research, Society and Development, 2020)
This research aims to reflect on the relationship between Central Auditory Processing Disorder and the process of learning to read and write from a psychopedagogical perspective. The literature review was adopted for this research in a described and qualitative approach. The results showed that the central auditory processing disorder (CAPD) constitutes a disorder that affects the understanding of sounds that reach the cerebral cortex, preventing the subject from being able to interpret them correctly, compromising the assimilation of the information received. So, the symptoms of CAPD can present as difficulties in reading and writing, slow response to sound stimuli, lack of understanding of what is heard, inattention, among others. It is concluded that, the early diagnosis, carried out by professionals qualified in the field of audiology, contributes for the subject with CAPD to recover their hearing skills fully or partially, enabling the development in the learning of this subject in a satisfactory way, even improving your self-esteem. And that through psychopedagogical intervention it is possible to obtain a satisfactory result that meets the needs of this subject, collaborating significantly in the construction of his learning.